2023
DOI: 10.1108/gm-12-2021-0386
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a critical mass of women on boards to reduce the gender pay disparity among non-executive directors

Abstract: Purpose The interest in promoting diversity in corporate governance is increasing gender equality on boards. Even so, previous research shows that women are underrepresented on boards of directors. This study aims to explore how an increasing presence of women on boards reduces gender pay disparity among nonexecutive directors (NEDs). Design/methodology/approach This study explores how an increasing presence of women on boards reduces gender pay disparity among NEDs. Findings The results indicate that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…In contrast, women in nomination committees significantly negatively affect say-on-pay dissent voting. This is supported by research by Tarkovska et al (2023) who found that the presence of women on committees would further reduce the wage gap. Singhania et al (2022) found the presence of women on the nomination and remuneration committee significantly increased Tobin's q but decreased ROA.…”
Section: Diversity Of Gender Nationality and Race (Skin Color) In The...mentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast, women in nomination committees significantly negatively affect say-on-pay dissent voting. This is supported by research by Tarkovska et al (2023) who found that the presence of women on committees would further reduce the wage gap. Singhania et al (2022) found the presence of women on the nomination and remuneration committee significantly increased Tobin's q but decreased ROA.…”
Section: Diversity Of Gender Nationality and Race (Skin Color) In The...mentioning
confidence: 76%
“…In contrast, women in nomination committees significantly negatively affect say-on-pay dissent voting. This is supported by research by Tarkovska et al. (2023) who found that the presence of women on committees would further reduce the wage gap.…”
Section: Dimensions Of the Nomination And Remuneration Committeementioning
confidence: 76%
“…More recently, studies such as Alves (2023) and Ssekiboobo et al (2023) demonstrated that gender diversity on the board is useful in reducing managerial opportunism. Furthermore, Tarkovska et al (2023) results indicate that the presence of women on the board may influence salary justice, reducing inequalities. Given this, it's possibe to recognize the benefits of gender diversity on boards and it can be considered that the existence of more diverse boards reduces managerial opportunism, resulting in a abnormal compensation reduction.…”
Section: Gender Diversity On the Board Of Directorsmentioning
confidence: 95%
“…The research on gender pay issues among non-executive remuneration within the same board has been given little academic attention and mainly focused on board levels, as a percentage of female board members. Only a few studies have considered the influence of gender at the level of individual non-executive directors and documented the gender pay gap in general (Hahn and Lasfer 2011;Tarkovska et al 2023;Marchetti and Stefanelli 2009;Bugeja et al 2014;Goh and Gupta 2016;Fedaseyeu et al 2018;Belcredi and Bozzi 2019). However, the specific role that female non-executive directors play on the board is not taken into account in these studies.…”
Section: H2mentioning
confidence: 99%